Red Travellers: Jeanne Corbin and Her Comrades - Lévesque, Andrée (McGill-Queen's University Press, 2006)
Jeanne Corbin typifies the female militants of the first generation of Canadian Communists. Andrée Lévesque's powerful account of the experiences of Corbin and her female comrades reveals the essential role women played in the movement. Levesque also shows that, despite some efforts to construct egalitarian gender relations, these women subordinated gender issues to the class struggle. Corbin's red itinerary began when she joined the Young Communist League in Edmonton. She later held party posts across the country through her involvement with The Worker in Toronto, a French communist paper in Montreal, the Workers' Cooperative in Timmins, and a lumbermen's strike in Abitibi - where she was jailed for taking part in a protest. She died of tuberculosis in London, Ontario, in 1944. Levesque relies on a wide range of sources to provide a unique exploration of Canadian labour and social history. –Publisher's descriptioin
Book available at Internet Archive to people with print disabilities: https://archive.org/details/redtravellersjea0000leve OCLC: 778049214